LITERASI MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) - Manoy, Janet Trineke; Sari, Marinda Rosita (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
contenxts. This study aims to describe the mathematical literacy of class X high school students in solving PISA questions. Date collection wa carried out using tests and interviews. 2 questions level 4dan level 6 are given to students. Date analysis is based on PISA mathematical process indicators namely formulating, applying, and interpreting. The results showed that: in the process of formulating, students mentioned important information in the problem, how to slove it and what concepts would be used, as well as what was know and asked in the problem. In the process of applying students to design and implement strategies according to the information they have made, draw the required objects according to the questions given. In the process of interpreting, students explain the reasons why the conclusions they get are in accordance with the context of the problem given.